ANALISA KESIAPSIAGAAN MASYARAKAT PAUH DALAM MENGHADAPI PERMASALAHAN KESEHATAN PASCA BENCANA BANJIR BANDANG : PERSPEKTIF PENERAPAN MANAJEMEN BENCANA - Afni, Yul (Menara Ilmu, 2018)
The high potential of natural disasters in West Sumatra, especially of Padang is basically areflection of the geographical conditions which is very unique because it is located at themeeting of three tectonic plates of the world. Pauh district is one of 7 districts prone to flooddisasters, especially Flash Floods (Banjir Bandang). Flash Flood is a massive flood thatcomes suddenly with overflowing, flooding, and pouring down large objects (such as woodand so on). The number of problems that occur after Flash Floods associated with healthproblems into things that will follow and must be faced by the community. It should beenforced good disaster management one of them public preparedness in facing healthproblems after Flash Floods need to be known. The high level of community knowledge aboutFlash Floods disasters and their preparedness in the face of disasters and accompanyingissues such as health problems is very high at 70% although the education background of themajority of the population is only the primary school level, due to the experience of FlashFloods disaster. The level of knowledge is what makes good attitude and action of communityparticipation in minimizing health risk after banjir bandang happened. On the other hand,community preparedness measures are considered not good because of the low averageincome.Key words: natural disasters, management disasters, flash floods, preparedness